2016
DOI: 10.4097/kjae.2016.69.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying brain monitoring during anesthesia: limitations, possible improvements, and perspectives

Abstract: Currently, anesthesiologists use clinical parameters to directly measure the depth of anesthesia (DoA). This clinical standard of monitoring is often combined with brain monitoring for better assessment of the hypnotic component of anesthesia. Brain monitoring devices provide indices allowing for an immediate assessment of the impact of anesthetics on consciousness. However, questions remain regarding the mechanisms underpinning these indices of hypnosis. By briefly describing current knowledge of the brain's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…In present endoscopic surgery instruments must avoid vital vessels and avert damage to tissue around the wound. 58,59) Here we choose the 0.7 mm needle, which is close to the mainstream diameter endoscope adopt by clinical surgery 60) and we did not observe any side-effect conditions, such as haemorrhage and death. Previous studies suggested that all kinds of trauma could influence neural function in a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In present endoscopic surgery instruments must avoid vital vessels and avert damage to tissue around the wound. 58,59) Here we choose the 0.7 mm needle, which is close to the mainstream diameter endoscope adopt by clinical surgery 60) and we did not observe any side-effect conditions, such as haemorrhage and death. Previous studies suggested that all kinds of trauma could influence neural function in a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…neuromuscular blocking agents), and brain ischaemia, have a significant effect on raw EEG data. Additionally, DoA monitors are limited by their calibration range and inter patient variability in dose response curves..." [186]. These limitations and interactions can degrade the performance of manual infusion systems and will nodoubt impose challenges to high-quality closed-loop control of anesthesia.…”
Section: A Monitoringmentioning
confidence: 99%
“…These limitations and interactions can degrade the performance of manual infusion systems and will nodoubt impose challenges to high-quality closed-loop control of anesthesia. Recently, patient state index (PSI) algorithm-based devices have been considered as alternatives to BIS monitors for their high sensitivity to variations in sedation/hypnosis and uniform response to various anesthetic agents [186], [187]. Although the PSI devices have some advantages to classical EEG monitors, including reduced sensitivity to noise, the PSI index is more sensitive to interpatient variability than BIS [188] and may be affected by EMG signals [186], [189].…”
Section: A Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that GA is associated with decrease in the coherences in several frequency bands (John et al, 2001). The medial prefrontal cortex and posterior cingulate/precuneus region have been found to be two of the brain areas most sensitive to anaesthetics (Vogt & Laureys, 2005;Boveroux et al, 2010;Cascella, 2016). The observed changes in DMN connectivity during loss of consciousness and alteration of external awareness mean that DMN integrity may represent the level of consciousness.…”
Section: Introductionmentioning
confidence: 99%